(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
New interpretation (of sections) of five Celtiberian inscriptions (1st and 3rd Bronze from Botorrita, Oinochoe from Caminreal, Vase from Albacete and a square bronce leaf of uncertain procedence) based on the identification of the verbal stem auz- with the normal grade of the Indo-European root *h2ews- meaning ‘to scoop up, to draw water’. While the two vases reveal themselves as more or less classical examples of ‘speaking vessels’, the bronze inscriptions belong to the public sphere. In particular, the hitherto obscure Third Bronze from Botorrita appears to be a list of people entitled to draw water from a newly built channel-system. The proposal can also shed some light on one element of the newly found lead inscription from Cuenca.